Effect of caffeine on mitochondrial biogenesis in the skeletal muscle – A narrative review. (October 2022) - Yamada, André K.; Pimentel, Gustavo D.; Pickering, Craig; Cordeiro, André V.; Silva, Vagner R.R.
Summary: Caffeine is one of the most widely used substances as recreational drug for performance-enhancement in sport, underpinned by a strong evidence base. Although the effects of caffeine are widely investigated within the scope of performance physiology, the molecular effects of caffeine within skeletal muscle remain unclear. Evidence from in vitro and in vivo models suggest that caffeine regulates the glucose metabolism in the skeletal muscle. Moreover, caffeine seems to stimulate CaMKII, PPARδ/β, AMPK and PGC1α, classical markers of exercise-adaptations, including mitochondrial biogenesis and mitochondrial content. This review summarizes evidence to suggest caffeine-effects within skeletal muscle fibers, focusing on the putative role of caffeine on mitochondrial biogenesis to explore whether caffeine supplementation might be a strategy to enhance mitochondrial biogenesis.